Criterios para la aplicación de la terminación anticipada en la etapa intermedia del proceso penal peruano. - Robles Quezada, Viviana Judith (2016)
This thesis investigated the criteria that justify the application of plea bargaining during the preliminary examination of peruvian criminal procedure, in order to highlight the great utility of this alternative, the need for its application and the benefits it brings to our Criminal justice system. The research was performed using the analytical-synthetic, inductive-deductive, hermeneutical-legal and comparative methods. Techniques such as documentary collection, normative interpretation, interview and descriptive statistics were used, which allowed the integration of variables for analysis. Also, a theoretical framework was developed regarding the most relevant legal figures of the thesis topic, which allowed to clearly identify and characterize each one of them. From the results and conclusions arrived at, the criteria for the application of plea bargaining during the preliminary examination of the criminal process were established, being these: simplification of the criminal process, procedural decongestion, support of the comparative legislation and The Model Criminal Procedure Code for Ibero-America, as well as the possibility of its delineation of Plenary Agreement N° 5-2009/CJ-116.